Comparison of different metrics of cerebral autoregulation in association with major morbidity and mortality after cardiac surgery. (July 2022) - Liu, Xiuyun; Donnelly, Joseph; Brady, Ken M.; Akiyoshi, Kei; Bush, Brian; Koehler, Raymond C.; Lee, Jennifer K.; Hogue, Charles W.; Czosnyka, Marek; Smielewski, Peter; Brown, Charles H.
Abstract: Background: Cardiac surgery studies have established the clinical relevance of personalised arterial blood pressure management based on cerebral autoregulation. However, variabilities exist in autoregulation evaluation. We compared the association of several cerebral autoregulation metrics, calculated using different methods, with outcomes after cardiac surgery. Methods: Autoregulation was measured during cardiac surgery in 240 patients. Mean flow index and cerebral oximetry index were calculated as Pearson's correlations between mean arterial pressure (MAP) and transcranial Doppler blood flow velocity or near-infrared spectroscopy signals. The lower limit of autoregulation and optimal mean arterial pressure were identified using mean flow index and cerebral oximetry index. Regression models were used to examine associations of area under curve and duration of mean arterial pressure below thresholds with stroke, acute kidney injury (AKI), and major morbidity and mortality. Results: Both mean flow index and cerebral oximetry index identified the cerebral lower limit of autoregulation below which MAP was associated with a higher incidence of AKI and major morbidity and mortality. Based on magnitude and significance of the estimates in adjusted models, the area under curve of MAP < lower limit of autoregulation had the strongest association with AKI and major morbidity and mortality. The odds ratio for area under the curve of MAP < lower limit of autoregulation was 1.05 (95% confidence interval, 1.01–1.09), meaning every 1 mm Hg h increase of area under the curve was associated with an average increase in the odds of AKI by 5%. Conclusions: For cardiac surgery patients, area under curve of MAP < lower limit of autoregulation using mean flow index or cerebral oximetry index had the strongest association with AKI and major morbidity and mortality. Trials are necessary to evaluate this target for MAP management.